2017
DOI: 10.1080/00071668.2017.1415426
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and quantitative analysis ofCIDEaandCIDEcin broiler chickens: accounting for differential fat deposition between strains

Abstract: 1. Differences in the expression of CIDEa and CIDEc in 20 different tissues were examined. Both CIDEa and CIDEc mRNA transcripts were predominantly but variably expressed in white adipose tissue (WAT) but were also expressed at moderate levels in the kidney and liver and at lower levels in the ovary. Interestingly, among WAT types, both CIDEa and CIDEc were expressed at the lowest levels in heart coronary WAT. 2. To better understand the roles of CIDEa and CIDEc in the fat deposition of broiler chickens, the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…This result was consistent with the fact that in ammatory cell in ltration has been documented to commonly occur in adipose tissue and stimulate the activation of the immune defense system [50]. In addition, we also found that many pathways related to lipid metabolism (Cholesterol metabolism and Arachidonic acid metabolism) were signi cantly enriched for many DEMs, such as ADIPOQ, CIDEC, SOCS2, SCD and ACAA2, that have been reported to participate in lipid metabolism [51][52][53][54][55]. Many DEMs, such as C1QC, AGPAT4, SNCA and CAV3, were found to be related to lipid deposition for the rst time [56][57][58].…”
Section: Discussionsupporting
confidence: 89%
“…This result was consistent with the fact that in ammatory cell in ltration has been documented to commonly occur in adipose tissue and stimulate the activation of the immune defense system [50]. In addition, we also found that many pathways related to lipid metabolism (Cholesterol metabolism and Arachidonic acid metabolism) were signi cantly enriched for many DEMs, such as ADIPOQ, CIDEC, SOCS2, SCD and ACAA2, that have been reported to participate in lipid metabolism [51][52][53][54][55]. Many DEMs, such as C1QC, AGPAT4, SNCA and CAV3, were found to be related to lipid deposition for the rst time [56][57][58].…”
Section: Discussionsupporting
confidence: 89%
“…Cell death‐inducing DFF45‐like effector C (CIDEC) may be a key molecule in regulating renal apoptosis and autophagy deficiency induced by insulin resistance. Studie has shown the importance of CIDEC in regulating apoptosis 11 , 12 , 13 , 14 . Under the condition of high glucose, early growth response factor (EGR)1 can induce DN by enhancing extracellular matrix to deposit and mesangial cells to proliferate, partly due to TGF‐β1 upregulation mediated by EGR1 under high glucose conditions 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Most studies of Cidea and Cidec in fatty liver focused on mice and human. In poultry, our group's previous study showed that both Cidea and Cidec mRNA transcripts were predominantly but variably expressed in white adipose tissue (WAT), and Cidea and Cidec mRNA levels in white adipose and liver tissues were significantly higher in fat‐type broiler lines than in their lean counterparts (Huang et al., ). Our observations suggest that the functions of Cidea and Cidec reflect inherent characteristics of lipid metabolism that contribute to the differences in fat deposition between strains.…”
Section: Introductionmentioning
confidence: 99%